Implementasi Kurikulum Merdeka di SDIT Hasan Sanusi - Syaiful Alim (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2026)
This study aims to analyze the implementation of the Merdeka Curriculum in an Islamic Integrated Elementary School (SDIT Hasan Sanusi Catakgayam Mojowarno) during the 2024/2025 academic year. The research employed a qualitative approach using a single case study design. Data were collected through in-depth interviews, classroom observations, and document analysis involving teachers, school leaders, students, and parents. The findings indicate that the implementation of the Merdeka Curriculum has been carried out gradually and systematically by integrating the Pancasila Student Profile with Islamic values, such as faith (tauhid), moral character (akhlak), and Qur’anic memorization. Project-Based Learning (P5) was implemented contextually and contributed to increased student engagement and character development. Supporting factors included teacher training, school leadership commitment, and adequate infrastructure, while constraints were limited funding, varying levels of parental involvement, and teachers’ adaptation in designing contextual learning modules. This study concludes that the Merdeka Curriculum can strengthen Islamic education when implemented flexibly and contextually. The findings contribute theoretically to curriculum implementation studies in Islamic education and practically offer recommendations for Islamic schools in adapting national curriculum reforms.